Examining the Role of Ataxin-2 Protein and its Domains in Cellular Function, Translational Control and Neurodegeneration - Petrauskas, Arnas (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2023)
Ataxin-2 (ATXN2) is a gene implicated in spinocerebellar ataxia type II (SCA2), amyotrophic lateral sclerosis (ALS) and Parkinsonism. The encoded protein is a therapeutic target for ALS and related conditions. ATXN2 (or Atx2 in insects) can function in translational activation, translational repression, mRNA stability and in the assembly of mRNP-granules, a process mediated by intrinsically disordered regions (IDRs). Our work has shown that the C-terminal IDR of Atx2 is essential for both long-term habituation and degeneration model progression in flies. On the other hand, we subsequently show the structured LSm domain, which can help stimulate mRNA translation, antagonizes mRNP-granule assembly. We built on previous research through a series of experiments on Drosophila and human Ataxin-2 proteins to highlight a poly-A tail ? polyA-binding protein (PABP) ? Atx2 interaction driven localisation mechanism for the protein. Results of Targets of RNA-Binding Proteins Identified by Editing (TRIBE), co-localization and immunoprecipitation experiments indicate that the PABP interacting, PAM2 motif of Ataxin-2 may be a major determinant of the mRNA and protein content of Ataxin-2 mRNP granules. Transgenic experiments in Drosophila indicate that while the Atx2-LSm domain may protect against neurodegeneration, structured PAM2- and unstructured IDR- interactions both, through distinct modes of action, support Atx2-induced cytotoxicity. Examining radically truncated Atx2 constructs in cells and transgenic flies allowed to separate and independently assay the effects of structured and unstructured domains and their respective interactions. Taken together, the data lead to a proposal for how Ataxin-2 interactions are remodeled during translational control and how structured and non-structured interactions contribute differently to the specificity and efficiency of RNP granule condensation as well as to neurodegeneration, with powerful implications for future therapeutic approaches.
APPROVED
Keywords: Ataxin-2; ATXN2; TRIBE; mRNA; PABP; Disordered Regions; Protein Domains; IDR; Subcellular Organization; Granules; Stress Granules; Neurodegeneration; RNP Granules; Drosophila; Cell Biology